Longitudinal trajectories of eating disorder symptoms in mothers: the predictive role of PTSD and childhood trauma - Helle, Sofie Egidius; Wangsmo, Pernille Telstad; Stänicke, Line Indrevoll; Vrabel, KariAnne R. (Frontiers in Psychology, 2025)
ObjectiveA significant sub-group of patients with eating disorders (ED) are mothers. There is limited literature on this population, and little is known about their treatment trajectories and outcomes. The primary objectives of this study were to examine; (1) longitudinal changes in ED symptomatology among mothers who underwent a specialized sequential treatment, and (2) the extent to which post-traumatic stress disorder (PTSD) and/or childhood trauma predicted treatment outcome.MethodsA total of 61 patients with ED received a highly specialized, sequential inpatient Cognitive Behavior Therapy (CBT) program for mothers delivered over 6 weeks in total, with one treatment week per month across a six-month period. ED symptoms were measured with Eating Disorder Examination-questionnaire (EDEQ) at admission, discharge, and 1-year follow-up. Data were analyzed with multi-level analysis, and we examined outcomes for both overall symptom reduction, as well as for the four clinical subscales that EDE is comprised of, e.g., “Weight concern,” Shape concern, Eating Concern, and Restriction.ResultsThere was a significant reduction in ED symptoms from admission to discharge, which remained stable through the 1-year follow-up. PTSD and childhood trauma predicted the level of “Shape concern” negatively across the entire period. PTSD also predicted the level of “Weight concern” negatively over time.DiscussionSpecialized sequential treatment for mothers with ED shows potential role as a promising intervention. However, further research is needed to confirm its effectiveness. Additionally, this study enhances our understanding of the role of trauma in the treatment of ED.